2017
DOI: 10.21037/jss.2017.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of minimally invasive percutaneous thoracolumbar pedicle screws using 2D fluoroscopy: a retrospective review through 3D CT analysis

Abstract: Background: In the literature, there is a large variation in the reported misplacement rates of pedicle screws.The use of minimally invasive surgical techniques is increasing and as such there has only been a small amount of data to look at the misplacement rate of percutaneously inserted thoracic and lumbar pedicle screws.Methods: A retrospective analysis of post-operative computed tomography (CT) scans were performed on 108 patients who underwent minimally invasive percutaneously inserted thoracic and lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Misplaced screws are not only biomechanically disadvantageous but also carry an increased risk for neurological deficit, vascular damage, and morbidity [1][2][3]. Advances in imaging and navigation such as fluoroscopic guidance have improved the accuracy of screw placement in the spine, yet significantly increased the amount of radiation exposure to the patient, surgeon, and operating room (OR) staff [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Misplaced screws are not only biomechanically disadvantageous but also carry an increased risk for neurological deficit, vascular damage, and morbidity [1][2][3]. Advances in imaging and navigation such as fluoroscopic guidance have improved the accuracy of screw placement in the spine, yet significantly increased the amount of radiation exposure to the patient, surgeon, and operating room (OR) staff [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the complication of pedicle screw misplacement is concerning with the freehand approach, especially in thoracic and cervical spine region. Winder et al reported that a misplacement rate of thoracic pedicle screws is 14.67% (12). Amiot et al reported…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, comparison of maldirected screws (classes 2 and 3 collectively) between the two groups confirmed a statistically high significant difference in the number of maldirected screws per patient (P<0.001). Idler et al, 10 Mark et al, 15 and Tsuang et al, 14 reported better results regarding the number of cortical breaches complicating percutaneous lumbar screws placements with an overall accuracy of 98.47%, 97.7% and 94.1% respectively while Spitz et al, 13 reported an overall accuracy of 96.7%. On the other hand, Mohi Eldin et al, 11 reported an accuracy rate that was comparable to that reported in the current study (79.4% versus 81.25 % respectively) regarding the percutaneous group.…”
Section: Discussionmentioning
confidence: 99%
“…Screw misplacement carries the risk of having an inadequate construct, unintended durotomy and, moreover, an incidence of inadvertent neurological injury of 1%-11%. 5,12,15 Currently, there are three methods for pedicle screw placement: the free hand, the fluoroscopy guided open and the percutaneous techniques with the fluoroscopy guided open technique being the most frequently used one. 3,7,16 The traditional open technique has been always believed to have the disadvantage of extensive paraspinal muscles dissection and retraction for exposure of the necessary bony landmarks that may be a direct cause of more blood loss and a prolonged postoperative hospital stay and recovery time especially from pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation